Roles of c-Fos, EGR-1, PKA, and PKC in cognitive dysfunction in rats after propofol anesthesia (Brazilian Journal of Pharmaceutical Sciences, 2022)
This study aimed to investigate possible changes in the spatial memory of rats and the expression or activity of EGR-1, c-Fos, PKA, and PKC after propofol anesthesia. Thirty-six Sprague-Dawley rats aged 20 months and 36 Sprague-Dawley rats aged three months were each randomly divided into three groups: the control group, the Morris Water Maze (MWM) group, and the propofol group. In the propofol groups of both young and aged rats, the rats were anesthetized by propofol for two or four hours and then performed the MWM test two days or two weeks after anesthesia to assess cognitive function. EGR-1, c-Fos, PKA, and PKC expressions in the rat hippocampus were determined via immunohistochemistry. For the older rats, the escape latency in the P4h/2d group was significantly prolonged (P < 0.05), and the learning curve was right-shifted in the P4h/2w group (P < 0.05). The expression levels of EGR-1, c-Fos, PKA, and PKC in the MWM groups were significantly higher than those in the control groups (P < 0.05). In the P4h/2d group of aged rats, the expression levels of both PKA and PKC were decreased compared with those of the MWM groups. The decreased expression of both protein kinases may be responsible for the observed impairment after propofol anesthesia.